AROLOC: Advanced & Robust 3-D Localization in Wireless Sensor Networks - A V, Kalpana; Rukmani Devi, S; S, Vinod (International Journal of Engineering and Technology, 2018)
Over the past few years, tracking an object and finding a position is one of the day-to-day activities of our life. For finding the position and to tell that position is the accurate one, we need to rely on a novel localization method. Localization is nothing but a system that tells how to accurately find a position. The fundamental thought in most localization algorithm is that few nodes are inculcated with GPS, and are called as beacon nodes. Using the beacon nodes, other nodes localize themselves, which is a very basic concept in localization. The existing approaches tell that localization algorithm works based on finding out the accurate position in a 2-D environment even in the existence of malignant beacon nodes. Our aim is to suggest a new localization algorithm that is suitable for 3-D environment and that algorithm works even more efficiently in the presence of malignant beacon nodes which makes the system â€œrobustâ€. The performance of the system is compared with other 3-D approaches used for localization.Â